An Evaluation of Formal and Underlying Factors Influencing Student Participation within E-Learning Web Discussion Forums - Cramphorn, Christopher (Proceedings of the International Conference on Networked Learning, 2004)
This paper examines factors that may influence student participation within e-learning web discussion forums. The existing literature suggests that there are several factors, but the author suggests that they have missed a crucial underlying element; the constructivist nature of the forums themselves. The paper through analysis of a small scale empirical project examines how factors such as psychology, lack of social cues and the timescales required may all influence participation, but that the constructivist nature itself may assist or hinder students at different times in their development. Also the paper gives suggestions on how participation may be advanced.